Sostenibilidad del sector camaronero y su influencia socioeconómica en los cantones Sucre, San Vicente y Jama - Quijije Intriago, Martha Rocío (2021)
The purpose of the research is to evaluate the sustainability of the shrimp sector and its influence on the socioeconomic aspects of the Sucre, Jama and San Vicente cantons. Various research methods such as inductive-deductive, analytical-synthetic, statistical and Delphi were used. In addition, actions were carried out such as determining the variables and indicators of sustainable and socioeconomic development, where a panel of experts was formed, who selected the variables to evaluate with the application of the Delphi method and validated the reliability with the Kendall concordance method, reaching 0.82% and 0.92%, respectively. Then, the current situation of the selected shrimp farms was diagnosed, using the survey, a tool developed and validated by specialists with 0.99% reliability according to Cronbach's Alpha. A correlation and regression were performed on this information, where the positive and negative aspects of the selected indicators were verified, among which the deficiencies at the time of scheduling a medical appointment, and their attention to the health indicator were highlighted, adding to this that sometimes the effort and work of the employees is not valued, the same ones who do not have another income method affecting the poverty indicator, and the absence of waste control, which disturbs sustainability. All this information served for the elaboration of a methodological proposal based on the Balanced Scorecard model in order to align the current management of the shrimp farms of the Sucre, Jama and San Vicente cantons towards sustainability, in search of an equitable development that promotes the Social, economic and environmental well-being.